O comportamento da citricultura em Sergipe : análise de uma suposta crise no setor. - Barbosa, Aline Maria Rosa (2012)
The objective of this research was to evaluate the activity of citrus in Sergipe. To achieve the main focus of the subject matter we specifically had: to analyze the productivity of citrus sector of Sergipe, in its southern territory in the period between 1990 and 2009, to raise the socio-demographic aspects of the citrus farmer in that territory; to verify the characteristics of citrus properties; to identify the agricultural practices employed in these properties, to see the influence of climatic factors on the perception of citrus producers, and finally, to check the citrus growers' perception about the prospects for future growth of their business. The motivation and idea of this study was due to the citrus industry in Sergipe has been going through periods of change and instability since the mid-1990s. Thereafter, the producers, particularly the small ones, encountered marketing problems, and a systematic change of agricultural credit, which led to a growing debt. We also highlight other factors, including climate change, which combined with low efficiency of current systems of production, also contributed to the deepening crisis faced. Supported by a descriptive study with qualitative and quantitative approach, we sought to achieve the proposed objectives using published statistical data and interviews with 186 citrus growers of southern Sergipe. It was concluded that the alleged crisis in citrus Sergipe is a situation where there was a decrease in demand of orange and, consequently, a decrease in productivity. Thus, it was found that the so-called crisis has inhibited productivity of small farms, considering that the small producer is risk averse. The reason for this aversion comes down to the fact that these producers are deprived of resources and technical assistance. But the key factor that prevents the increase of productivity is the mentality of the citrus farmer not to face the property as a business.